Profile of Scientific Initiation students in Brazilian Federal Institutes: Research areas, gender, and scholarship type by region (Research, Society and Development, 2021)
Financial support and science promotion policies require preliminary studies of diagnoses, researcher profiles and historicity. Based on that new propositions to stimulate the areas of knowledge, the participation of researchers by gender or even the allocation of resources by region may be implemented. In this context, this study aims to describe the profile of the Scientific Initiation scholarship holders, through financial incentives from the Brazilian National Research Council (CNPq), in the Brazilian Federal Institutes (IFs), considering the type of scholarship, age and gender. A quantitative approach was used, and 2017 data were collected on the CNPq portal. The results show that, out of the total scholarships (n = 31,382), 8.75% of them were offered by FIs, with the majority of scholarships offered by the high school program (64.60%), followed by the technological development program (18.14%) and the scientific initiation program (17.26%). Most students are female (51.1%). Given the above, we emphasize the importance of studies on student profile, so that measures are taken to provide wider access to scholarships for students involved in Brazilian scientific production, as well as map the areas of greatest investment and development technological.